NONPARAMETRIC TEST FOR UBACT CLASS OF LIFE DISTRIBUTION BASED ON U-STATISTIC - Bkr, Mahmoud; Youssef S. E, Abu; M.E, Bakr (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
Based on U-statistic, testing exponentially versus used better than aged in convex tail ordering (UBACT) class of life distribution is introduced for complete and cen-sored data. Convergence of the proposed statistic to the normal distribution is proved. Selected critical values are tabulated for sample sizes 5(5)80 for complete data, and (61)(10)(201) for censored data: The Pitman asymptotic relative e¢ ciency of the pro- posed tests to the other classes is studied. A numerical examples in medical science demonstrates practical application of the proposed test .